Developing a location viewer for Residential Property System (ReProS) using spatial database / Farashazillah Yahya - Yahya, Farashazillah (2006)
Over the years, the importance of spatial databases is growing rapidly, partly as a result of the recognition that the applications extend well beyond the traditional domain of GIS. Location is a powerful way of identifying and characterizing information because many data sets have footprints m space. Obviously, for a residential area, information is worthless if there is lacking knowledge about its location. At this time, there are no help on gaining location maps of residential area in Malaysia websites. It is a particular problem for house buyers in retrieving information. On the other hand, developers confh)nt troubles in describing their new residential area. An analysis of user requirement by verifying the existing user requirement had proposed a spatial database design to encounter the situation. The creation of spatial database for the location viewer has enabled a development of a model. Presently it had been demonstrated as capable of viewing a location map and other location information. Precisely adding up, the location viewer model had assisted the user in retrieving more information of a residential area in terms of viewing a location map and measuring distance between the residential area and required facilities.